Trend of Changes in Quantitative and Qualitative Traits in the Next Generation of BC3F2 Genotype from Crosses of Parent of High Protein Corn with Local Waxy Corn - Edy, Edy; Takdir, Andi; Subaedah, St. (International Journal of Environment, Agriculture and Biotechnology, 2022)
Corn can be used as an alternative staple food, but it is underdeveloped because it generally does not taste fluffier like rice. Therefore, it is necessary to develop corn that tastes fluffier, has high protein and has high production. The purpose of this study was to determine the trend of changes in quantitative (production) and qualitative (protein and amylopectin levels) traits in the next generation of BC3F2 genotype from a cross between high protein maize parents (Srikandi Putih variety) and high amylopectin maize (Local variety of Waxy corn). Seeds of Waxy corn, Srikandi Putih Varieties, BC2F1 and BC3F1 will be used as basic materials in this study. The study was designed in the form of a Randomized Block Design. The treatments consisted of genotypes BC2F1, BC3F1, Srikandi Putih Variety and Local variety of Waxy Corn. For the BC3F1 genotype, 210 plants were self-treated to produce the BC3F2 genotype. The results showed that there was an increasing trend of high protein and production characters from the inheritance of the Srikandi Putih Variety to the BC3F1 and BC3F2 genotypes. This was supported by an increase in ear length, ear diameter, weight of 100 seeds, seed weight per plot and seed production per hectare and an increase in protein content. The same trend also occurred in the character of amylopectin levels from the inheritance of local waxy corn parents to the BC3F1 and BC3F2 genotypes which were increasing.